An investigation of the attitudes of visually impaired middle school students toward the environment - Maşide Güler; Mustafa Ürey (Journal of Pedagogical Research, 2022)
This study presents the results of a survey of eighty-seven visually impaired middle school students (including those who are blind and those who have low vision) concerning their attitudes toward the environment. The findings with respect to students' ecocentric, anthropocentric and antipathetic attitudes, as well as whether these attitudes differentiate according to gender, living environment, level of vision and family income, are reported. The students were found to be more likely to have an ecocentric attitude, and only the variable of family income had a significant impact on ecocentric attitudes. In line with these results, suggestions have been made for future research.